Being Connected in Hard Times The Ottoman and Zanzibar Relations in the Late 19th Century - UĞUR, HATİCE (My University, 2024)
This study focuses the relationship between the Ottoman Empire and the Zanzibar Sultanate within the broader context of late 19th-century East Africa, characterized by diverse actors and interactions. Through an examination of trans-local entanglements involving local, European, and Ottoman actors, the study aims to understand how two Muslim states developed relationships during the late 19th century as reflected in the Ottoman primary sources.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (Soc); Social Sciences (Soc); Ottoman Empire; Zanzibar Sultanate; East Africa; 19th century; colonialism; Ottoman sources